Using Effective Methods in Teaching a Young Artist Is a Pledge That Talented Young People Will Become Mature Specialists (Eurasian Research Bulletin, 2021)
At the moment, attach a sizable significance to group quality training specialists toward science and technology. Using leading methods for teaching fine arts helps talents to become well-qualified professionals.